Research on Fresh and Hardened Sealing Slurries with the Addition of Magnesium Regarding Thermal Conductivity for Energy Piles and Borehole Heat Exchangers - Tomasz Sliwa; Tomasz Kowalski; Dominik Cekus; Aneta Sapińska-Śliwa (Energies, 2021)
Currently, renewable energy is increasingly important in the energy sector. One of the so-called renewable energy sources is geothermal energy. The most popular solution implemented by both small and large customers is the consumption of low-temperature geothermal energy using borehole heat exchanger (BHE) systems assisted by geothermal heat pumps. Such an installation can operate regardless of geological conditions, which makes it extremely universal. Borehole heat exchangers are the most important elements of this system, as their design determines the efficiency of the entire heating or heating-and-cooling system. Filling/sealing slurry is amongst the crucial structural elements. In borehole exchangers, reaching the highest possible thermal conductivity of the cement slurry endeavors to improve heat transfer between the rock mass and the heat carrier. The article presents a proposed design for such a sealing slurry. Powdered magnesium was used as an additive to the cement. The approximate cost of powdered magnesium is PLN 70–90 per kg (EUR 15–20/kg). Six different slurry formulations were tested. Magnesium flakes were used in designs A, B, C, and magnesium shavings in D, E and F. The samples differed in the powdered magnesium content BWOC (by weight of cement). The parameters of fresh and hardened sealing slurries were tested, focusing mainly on the thermal conductivity parameter. The highest thermal conductivity values were obtained in design C with the 45% addition of magnesium flakes BWOC.